AKIBAT HUKUM PERJANJIAN JUAL BELI RUMAH MELALUI KREDIT PEMILIKAN RUMAH SECARA OVER CREDIT DI BAWAH TANGAN - Mahfudzotin Nikmah; Hari Sutra Disemadi; Ani Purwanti (JCH (Jurnal Cendekia Hukum), 2020)
This research aims to examine the transfer of housing Mortgages (KPR) by transferring loans (over credit). This problem is caused by the lack of public knowledge about existing legal regulations related to buying and selling KPR by Over Credit. The research method used is a normative legal research method with a statutory approach and conceptual approach. The results of this research show that the process of over credit under the hand can be detrimental to third parties or substitute debtors. The loss was caused by the KPR organizer bank refusing to submit the KPR house certificate and the substitute debtor could not carry out the process of changing ownership of the land certificate for the KPR house he bought because the certificate was still registered in the name of the first party. Therefore, the settlement for the loss can be made by filing a lawsuit through the District Court with a verdict that has permanent legal force regarding the validity of the sale and purchase of mortgages under the hand and the third party is given the authority and power to use as appropriate.